Occurrence of the largetooth sawfish Pristis pristis (Linneaus, 1758) in northern Peru - Cabanillas-Torpoco, Mariano; Castillo, Deysy; Siccha-Ramírez, Raquel; Forsberg, Kerstin; Purizaca, Wilmer; Maceda, Martín (Zootaxa, 2020)
The largetooth sawfish (Pristis pristis) is listed as Critically Endangered on the IUCN Red List (Kyne et al. 2013). This species has been recorded in the Eastern Tropical Pacific, where its range has been described as extending from Mazatlan, Mexico, to northern Peru (Chirichigno & Cornejo 2001). Recent research efforts suggest that largetooth sawfish are now extremely rare or locally extinct on Mexico’s Pacific coast (Bonfil et al. 2018). There is no current information on the status of largetooth sawfish in Panama or Colombia; the most recent record of a largetooth sawfish captured on Colombia’s Pacific coast occurred in 2007 (Chasqui et al. 2017). In Ecuador, the species had been considered extirpated. However, in 2014, a large largetooth sawfish was captured by local fisherman in southern Ecuador, taken to the fishing port of Salinas and then released by the environmental agency (Barriga 2012; Rosas-Luis 2014). In Peru, recent reports of largetooth sawfish have been rare, but two captures of largetooth sawfish by fishermen (2014 and 2015) in northern Peru were reported (Mendoza et al. 2017). This confirms that the species is still occasionally encountered in this region.